ANALISIS PENGARUH STABILITAS INSTITUSI KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Permata, Indah Dian; Pangestuty, Farah Wulandari (Contemporary Studies in Economic, Finance and Banking, 2022)
The stability of financial institutions can be seen from the sound banking conditions and the functioning of the banking intermediation function in mobilizing public deposits so that they can be channeled in the form of credit and other financing to the business world. Financial institutions have an impact on the ecThe stability of financial institutions can be seen from the sound banking conditions and the functioning of the banking intermediation function in mobilizing public deposits so that they can be channeled in the form of credit and other financing to the business world. Financial institutions have an impact on the economy because banks can improve the national economy by increasing the efficiency of the use of funds and assisting the traffic of funds through payment services. This study aims to determine the influence of financial institutions on economic growth in Indonesia. The variables used in this study are NPL, LDR, CAR and JIBOR as indicators of financial institutions, while economic growth is reflected by GDP. The research model used is the Error Correction Model (ECM) with a significance level of 5%. The results show that in the short term NPL has a significant and different relationship with the movement of economic growth while the other variables have no significant or small relationship to the movement of Indonesia's economic growth, in the long term the JIBOR and CAR variables have no significant or significant relationship. small to the movement of the Indonesian economy then other macroeconomic variables in this study, namely NPL, LDR and DKG are known to have a significant and different relationship with the movement of economic growth.